JOB SATISFACTION AND JOB ROTATION SYSTEMS IMPLEMENTATION FOR COMPANY EMPLOYEES - Deddy Novie Citra Arta; Ashur Harmadi; Samuel PD Anantadjaya; Abu Bakar; Tuti Fitriani (SEAN Institute, 2023)
Job rotation policy is a strategy for developing employee skills by the company to improve employee performance, and this can provide refreshment and a sense of a new atmosphere for employees. So that it can provide job satisfaction or satisfaction to employees. The method in this research is a literature study by reviewing some of the results of previous research which originates from national and international articles. The research results were analyzed and used as material for discussion to determine answers to problems regarding the relationship between job rotation policies and job satisfaction which can have an impact on employee performance. All ideas from each study provide information about the methodologically desirable theory of the study being analyzed. The results of the literature review show that the job rotation policy implemented by the company has a good impact on employee job satisfaction, so it is good for improving employee performance.